A Post-Colonial Assessment of Indian Nationalism in Tagore’s Selected Novels - Ebenezer, Huldahrajammal (2005)
This paper is an investigation into the history of India during the early nineteenth century with the birth of the Indian Nationalist Movement under the British colonizers. It is a post-colonial reading and it is in close relation to Rabindranath Tagore who was an active participant in the nationalist movement and his manifold reasons for his disapproval of the movement.